Zakho City Model of Coexistence and Rejection of Inter-Religious Extremism : "An Analytical Descriptive Study" - Mohammed, Shawkat (Humanities Journal of University of Zakho, 2021)
Kurds are considered one of the ancient and live nations in the region. Their land, Kurdistan, is the cradle of the humanity and civilization for the entire world in general and for Islam and Muslims in particular. This paper studies Zakho as the best example for coexistence and the eradication of extremism among all religions and other beliefs. The study provides proofs and evidence that the Kurdish community is a peaceful community and Kurds believe in living in peace and coexistence, they try to eradicate the extremism, and guarantee a peaceful atmosphere for people from other religions and beliefs. Moreover, Kurds are also very kind and generous when dealing with non-Muslims. One of the traits that Kurds have is that almost all of them have the charity and giving souls; this is witnessed and proved now and in the past. The paper is consisted of three parts which are: First part: Background details and information about Zakho and its vicinities. Second part: Zakho as the best example for coexistence and the eradication of extremism and its effects. Conclusion: The results of the research and reference list.